Correlation of capillary zone electrophoresis with continuous free-flow zone electrophoresis: application to the analysis and purification of synthetic growth hormone releasing peptide - Prusík, Z; Kasicka, V; Mudra, P; Stĕpánek, J; Smékal, O; Hlavácek, J (Electrophoresis, 1990)
Two carrier-free electrophoretic separation methods, capillary zone electrophoresis (CZE) and continuous free-flow zone electrophoresis (FFZE), have been applied to both microanalysis at the nanogram level and preparative fractionation, with a throughput of 30 mg/h, of synthetic growth hormone releasing peptide (GHRP). A crude product of GHRP, a hexapeptide with the sequence His-D-Trp-Ala-Trp-D-Phe-Lys-NH2, synthesized by the solid phase methodology, was desalted and analyzed by CZE. Based on the results of analytical CZE the separation was converted into a preparative purification procedure by continuous FFZE, employing the same separation medium (0.5 mol/L acetic acid, pH 2.6). The purifity of peptide fractions obtained by FFZE was reevaluated by CZE. The combination of these two techniques proved to be a valuable tool for both peptide analysis and peptide purification. A close correlation of CZE and FFZE, resulting from the fact that both methods are based on the same separation principle (zone electrophoresis) and that both are performed in a free solution of the same composition, was confirmed. However, when transforming data from CZE to FFZE, the different electroosmotic flow, temperature and electric field intensity in the capillary and in the flow-through cell, respectively, have to be taken into account and corresponding corrections have to be made.
Keywords: Phenols; molekulární sekvence - údaje; elektroforéza; hormony; Amino Acid Sequence; difuze; Hormones; Growth Hormone-Releasing Hormone; Diffusion; fenoly; Molecular Sequence Data; Electric Conductivity; elektrická vodivost; oligopeptidy; Electrophoresis; Oligopeptides; sekvence aminokyselin; hormon uvolňující růstový hormon